2022
DOI: 10.3389/fmed.2022.830754
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilia and Lung Cancer: Analysis From Real-World Data and Mendelian Randomization Study

Abstract: Background and ObjectiveGrowing evidence added to the results from observational studies of lung cancer patients exhibiting eosinophilia. However, whether eosinophils contributed to tumor immune surveillance or neoplastic evolution was unknown. This study aimed to analyze the causal association between eosinophilia and lung cancer.MethodsThe causal effect of eosinophil count on lung cancer from a genome-wide association study (GWAS) was investigated using the two-sample Mendelian randomization (MR) method. Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In this context, 2SMR has provided the scientific community with tools to use IMD-associated SNPs as IVs to study the effect of IMDs on different cancers, based on the results of large and independent GWAS. For example, 2SMR strategies have identified (1) multiple sclerosis (MS) [ 51 ] and eosinophilia [ 52 ] as risk factors for lung cancer, (2) different levels of cytokines as risk or protective factors for multiple malignancies [ 53 ], and (3) systemic lupus erythematosus as a risk factor for lymphoma [ 54 ]. It is remarkable that the estimated risk effects of CeD on lymphoma in this study (OR > 1.7, Table 2 ) are in the range of the previously observed risk effects of proinflammatory cytokines on specific cancers [ 53 ], but considerably stronger than the effects of other IMDs [ 51 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, 2SMR has provided the scientific community with tools to use IMD-associated SNPs as IVs to study the effect of IMDs on different cancers, based on the results of large and independent GWAS. For example, 2SMR strategies have identified (1) multiple sclerosis (MS) [ 51 ] and eosinophilia [ 52 ] as risk factors for lung cancer, (2) different levels of cytokines as risk or protective factors for multiple malignancies [ 53 ], and (3) systemic lupus erythematosus as a risk factor for lymphoma [ 54 ]. It is remarkable that the estimated risk effects of CeD on lymphoma in this study (OR > 1.7, Table 2 ) are in the range of the previously observed risk effects of proinflammatory cytokines on specific cancers [ 53 ], but considerably stronger than the effects of other IMDs [ 51 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils could promote the adverse effect of tumour metastasis [ 29 ]. Besides, eosinophilia may be a potential causal risk factor in squamous cell lung cancer progression in the East Asian population, while the association between eosinophil counts and lung cancer was not significant in the European population [ 30 ]. To date, there is no related literature to report the relationship between eosinophils and HCC.…”
Section: Discussionmentioning
confidence: 99%
“…By knocking out eosinophils in mouse model, they found that the number of tumor metastases was elevated in mice with in ammation 29 . Wang et al suggested that eosinophilia may be a potential causal risk factor in the progression of squamous cell lung cancer in East Asian population, while the association between eosinophil counts and lung cancer was not signi cant in the European population 30 . To date, there is no related literature to report the relationship between eosinophils and HCC.…”
Section: Discussionmentioning
confidence: 99%